+0

# Integral

0
190
1

Please evaluate the following integral with steps, if possible: 1/ [3 sin(x) - 4 cos(x)]dx.

Thank you very much.

Guest Jun 16, 2017
Sort:

#1
+1

Take the integral:
integral1/(3 sin(x) - 4 cos(x)) dx
For the integrand 1/(3 sin(x) - 4 cos(x)), substitute u = tan(x/2) and du = 1/2 dx sec^2(x/2). Then transform the integrand using the substitutions sin(x) = (2 u)/(u^2 + 1), cos(x) = (1 - u^2)/(u^2 + 1) and dx = (2 du)/(u^2 + 1):
= integral2/((u^2 + 1) ((6 u)/(u^2 + 1) - (4 (1 - u^2))/(u^2 + 1))) du
Simplify the integrand 2/((u^2 + 1) ((6 u)/(u^2 + 1) - (4 (1 - u^2))/(u^2 + 1))) to get 1/(2 u^2 + 3 u - 2):
= integral1/(2 u^2 + 3 u - 2) du
For the integrand 1/(2 u^2 + 3 u - 2), complete the square:
= integral1/((sqrt(2) u + 3/(2 sqrt(2)))^2 - 25/8) du
For the integrand 1/((sqrt(2) u + 3/(2 sqrt(2)))^2 - 25/8), substitute s = sqrt(2) u + 3/(2 sqrt(2)) and ds = sqrt(2) du:
= 1/sqrt(2) integral1/(s^2 - 25/8) ds
Factor -25/8 from the denominator:
= 1/sqrt(2) integral-8/(25 (1 - (8 s^2)/25)) ds
Factor out constants:
= -(4 sqrt(2))/25 integral1/(1 - (8 s^2)/25) ds
For the integrand 1/(1 - (8 s^2)/25), substitute p = (2 sqrt(2) s)/5 and dp = (2 sqrt(2))/5 ds:
= -2/5 integral1/(1 - p^2) dp
The integral of 1/(1 - p^2) is tanh^(-1)(p):
= -2/5 tanh^(-1)(p) + constant
Substitute back for p = (2 sqrt(2) s)/5:
= -2/5 tanh^(-1)((2 sqrt(2) s)/5) + constant
Substitute back for s = sqrt(2) u + 3/(2 sqrt(2)):
= -2/5 tanh^(-1)((4 u)/5 + 3/5) + constant
Substitute back for u = tan(x/2):
= -2/5 tanh^(-1)(1/5 (4 tan(x/2) + 3)) + constant
Which is equivalent for restricted x values to:
Answer: | = 1/5 (log(cos(x/2) - 2 sin(x/2)) - log(sin(x/2) + 2 cos(x/2))) + constant

Guest Jun 16, 2017

### 2 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details